Workshop on Feminist Art Interventions: Shaping Spaces of Possibility through Co-Creative Action - Mittner, Lilli; Lotherington, Ann Therese; Lukic, Dragana (Septentrio Conference Series, 2019)
The workshop invites to a co-creative fine art session based on diffractive methodology, involving object handling, improvisation, and transformation. We come together without a detailed plan to create together and shed light on the processes involved, thereby “working with each other in our thinking practices” (Haraway 2016), keeping in mind the feminist idea of “living in difference together”. The session is an intertwinement of artistic practices, political activism and theoretical thinking, and builds on a concept developed within the Artful Dementia Research Lab. The session will last from 60 to 90 minutes, depending on decisions made by the group as we go along, and is followed by a conversation on connectivity, knowledge creation, tentacular thinking, power relations and relational aesthetics. The topics to be addressed derives from what we create together during the session. The workshop is arranged by the Artful Dementia Research Lab at the UiT’s Centre for Women’s and Gender Research, and part of the general program at the conference Kjønnsforskning NÅ!